The Effectiveness of Think Talk Write (TTW) Learning in Improving Students’ Mathematical Communication Ability - Kamaruddin Kamaruddin; Irvan Irvan (Journal of Education and Teaching Learning, 2023)
Learning mathematics is useful for students to be able to think critically, count, reason, and be able to analyze a problem. Not only that learning mathematics has an impact on improving mathematical communication skills related to everyday life. The purpose of this study was to test the effectiveness of using the Think Talk Write (TTW) learning model in improving students' mathematical communication skills at the junior high school level. This research took place at SMP Muhammadiyah 01 Medan. The population of this study was all students in class IX and the research sample was students in class IX-T1 at SMP Muhammadiyah 1 Medan, TA 2022/2023. This study used a quantitative pre-experiment design one-group pretest-posttest method. The test of mathematical communication skills is the instrument of this research. The research data was tested for its hypothesis using the paired sample t-test with the normality assumption test. While testing the effectiveness of increasing their mathematical communication skills using the N-Gain test.